G20 Digital Identity Onboarding - World Bank Group; Global Partnership for Financial Inclusion (World Bank, Washington, DC, 2018)
A unique, legal identity is necessary to allow all individuals to participate fully in society and the economy. The ability to prove one’s identity underlies the ability to access basic services and entitlements from healthcare through to pensions and agriculture subsidies. This is especially true for marginalized segments of society such as women, poor rural farmers, refugees and also extends to MSMEs (micro, small and medium enterprises). The importance of legal identity has been acknowledged by the international community through agreement of target 16.9 of the Sustainable Development Goals, which calls for all UN member States to “provide legal identity for all, including birth registration” by 2030.